Natural and anthropogenic organic brominated compounds in the southwestern Atlantic ocean: Bioaccumulation in coastal and oceanic dolphin species - Durante, Cristian Alberto (2024)
Marine pollution is considered a current driver of change in the oceans and despite the urgency to develop more studies, there is limited information in the southern hemisphere. This study aimed to analyze the levels and profiles of natural (MeO-PBDEs) and anthropogenic (BFRs: PBDEs, HBB, PBEB) organic brominated compounds in adipose tissue of two species of dolphins with different distribution and trophic requirements from the Southwestern Atlantic Ocean; the short-beaked common dolphin (Delphinus delphis) and the Fraser´s dolphin (Lagenodelphis hosei). In addition, we aim to investigate maternal transfer and biological pattern relationship (sex, age, sexual maturity) in short-beaked common dolphin bioaccumulation. The levels of both groups of contaminants were in the same order of magnitude as those reported for other marine mammals on both a regional and global scale. BFRs profiles were dominated by BDE 28 and BDE 47 in short-beaked common dolphin and Fraser´s dolphin, respectively, whereas 2-MeO-BDE 68 was the most abundant natural compound in both species. Evidence of maternal transfer, temporary increase in BDE 154 levels and no influence of sex, age, or sexual maturity on brominated compound concentration was observed in short-beaked common dolphin. This study fills a gap in the knowledge of the Southwestern Atlantic Ocean providing new information on emerging organic pollutants bioavailability for dolphins and, therefore, for the different trophic webs. In addition, it serves as a baseline for further contamination assessments.